On-the-Fly Monitoring of the Capture and Removal of Nanoplastics with Nanorobots - Velikov, Dean I; Jancik-Prochazkova, Anna; Pumera, Martin (ACS nanoscience Au, 2024)
Nanoplastics are considered an emerging organic persistent pollutant with possible severe long-term implications for the environment and human health; therefore, their remediation is of paramount importance. However, detecting and determining the concentration of nanoparticles in water is challenging and time-consuming due to their small size. In this work, we present a universal yet simple method for the detection and quantification of nanoplastics to monitor their removal from water using magnetic nanorobots. Nanoplastics were stained with a hydrophobic fluorescent dye to enable the use of photoluminescence techniques for their detection and quantification. Magnetic nanorobotic tools were employed to capture and subsequently remove the nanoplastics from contaminated waters. We demonstrated that nanorobots can capture and remove more than 90% of the nanoplastics from an aqueous solution within 120 min. This work shows that easy-to-use common fluorescent dyes combined with photoluminescence spectroscopy methods can be used as an alternative method for the detection and quantification of nanoplastics in water environments and swarming magnetic nanorobots for efficient capture and removal. These methods hold great potential for future research to improve the quantification and removal of nanoplastics in water, and it will ultimately reduce their harmful impact on the environment and human health.